Harnessing disorder: onychophorans use highly unstructured proteins, not silks, for prey capture - Haritos, Victoria S. (The Royal Society, 2010)
Onychophora are ancient, carnivorous soft-bodied invertebrates which capture their prey in slime that originates from dedicated glands located on either side of the head. While the biochemical composition of the slime is known, its unusual nature and the mechanism of ensnaring thread formation have remained elusive. We have examined gene expression in the slime gland from an Australian onychophoran, Euperipatoides rowelli, and matched expressed sequence tags to separated proteins from the slime. The analysis revealed three categories of protein present: unique high-molecular-weight proline-rich proteins, and smaller concentrations of lectins and small peptides, the latter two likely to act as protease inhibitors and antimicrobial agents. The predominant proline-rich proteins (200 kDa+) are composed of tandem repeated motifs and distinguished by an unusually high proline and charged residue content. Unlike the highly structured proteins such as silks used for prey capture by spiders and insects, these proteins lack ordered secondary structure over their entire length. We propose that on expulsion of slime from the gland onto prey, evaporative water loss triggers a glass transition change in the protein solution, resulting in adhesive and enmeshing thread formation, assisted by cross-linking of complementary charged and hydrophobic regions of the protein. Euperipatoides rowelli has developed an entirely new method of capturing prey by harnessing disordered proteins rather than structured, silk-like proteins.